A Diabetic Foot Survey - Ranjitkar, Sailaj; Pradhan, Eli; Paudel, Sujan; Pradhan, Shreya; Dhakal, Subodh (Journal of Diabetes and Endocrinology Association of Nepal, 2018)
Introduction: Diabetic foot has been defined by the International Working Group on the Diabetic foot and World Health Organisation as a Diabetic patient’s foot, associated with neuropathy, ischaemia or both, which has lead to ulceration, infection and/or deep tissue destruction An association of diabetic retinopathy with risk factors of Diabetic foot ulcer has been seen. Hence it is important to assess diabetic patients for risk factors leading to diabetic foot and tally these risks with diabetic retinopathy to help early diagnosis and management of diabetic foot and diabetic retinopathy. Methodology: This is a community based survey of a cohort of randomly presented patients examined on a first come first service basis limited to maximum of 100 patients to be reviewed in a day in a free health camp in Jaishi Dewal, Kathmandu, Nepal. The data of the patients were noted in a proforma documenting risks of diabetic foot and diabetic retinopathy. Results: Out of the 82 patients reviewed in the medical camp 38 were diabetic (type 2) with a mean age of 60.29 years being more common in females. Risk of Diabetic foot did have a definite association with level of education more common in the lesser educated and occupation (commonest in housewives). Awareness of risk of diabetic foot was only among 39.5% of the diabetic patients. Diabetic retinopathy was also seen only among 18.4% of the diabetic patients, being more common in the educated. Conclusion: Education and awareness programmes towards diabetic foot protocol are important despite the level of education or occupation. In diabetic patients, it is important to screen for risks of diabetic foot especially if patient has a history of hypertension and also screen for diabetic retinopathy.